2012
DOI: 10.1590/s0100-29452012000400034
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress change chlorophyll fluorescence in mango

Abstract: -This study evaluated the tolerance of mango cultivars 'Haden', 'Palmer', 'Tommy Atkins' and 'Uba' grafted on rootstock 'Imbú' to salt stress using chlorophyll fluorescence. Plants were grown in modified Hoagland solution containing 0, 15, 30, and 45 mmol L -1 NaCl. At 97 days the parameters of the chlorophyll fluorescence ( ') and ETR = (ΦPSII×PPF×0,84×0,5) were determined. At 100 days, the leaf emission and leaf area, toxicity and leaf abscission indexes were determined. In all cultivars evaluated, in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 15 publications
2
28
0
2
Order By: Relevance
“…This was found by Cavalcante et al (2010) for guava (Psidium guajava), Lucena et al (2012a) for mango trees (Mangifera indica L.) and Souto et al (2015) for noni (Morinda citrifolia). However, information on the behaviour of jackfruit under water or soil salinity, its germination process or any phenological phase of the plants is also very scarce.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…This was found by Cavalcante et al (2010) for guava (Psidium guajava), Lucena et al (2012a) for mango trees (Mangifera indica L.) and Souto et al (2015) for noni (Morinda citrifolia). However, information on the behaviour of jackfruit under water or soil salinity, its germination process or any phenological phase of the plants is also very scarce.…”
Section: Introductionmentioning
confidence: 56%
“…The losses in total dry matter resulting from an increase in salinity of the irrigation water from 0.3 to 4.0 dS m −1 were 42.49%, 51.91% and 54.52%, expressing the same sequence as for the effects on APDM: urea > ammonium sulfate > soil without N. Similar results were also found by Oliveira et al (2010); they concluded that association of saline irrigation water with nitrogen fertilization causes greater inhibition in total dry matter accumulation of plants when compared with soil without nitrogen. The reduction in dry matter of plants grown under saline conditions is mainly attributed to the nutritional imbalance caused by high levels of salts contained in the soil, reducing the absorption of essential nutrients such as potassium, calcium and phosphorus, and increasing the absorption of toxic elements (sodium and chlorine) by plants (CHEN et al, 2010;ELGHARABLY;MARSCHNER;RENGASAMY, 2010;LUCENA et al, 2012a). In these conditions, high doses of fertilizers, including nitrogen fertilizers which also contain salts, increase the salinity of the soil, compromising initial plant growth (CHEN et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…(Tabela 5), sendo o maior incremento observado no HTR-127, da ordem de 155 fotons. A fluorescência inicial explica a fluorescência quando a quinona, receptora primária de elétrons (QA) do fotossistema II (PSII), está totalmente oxidada e o centro de reação (P680) está aberto, indicando ativação das reações fotoquímicas (Munns & Tester, 2008;Lucena et al, 2012). Pode-se concluir que a salinidade afetou a atividade do fotossitema II dos híbridos nas primeiras 24 horas de submissão à salinidade, indicando o início da percepção do estresse a partir desse momento para todos os genótipos de citros estudados (Tabela 5), o que permite dizer que esta é uma das variáveis recomendadas para avaliação do início do estresse.…”
Section: Resultsunclassified
“…For Freire et al (2014), the reduction in the variable fluorescence of chlorophyll a of the plants evidences that the analyzed abiotic conditions lead to damages in the photosynthetic apparatus, compromising the PSII over the time of exposure to the stress factor of the stress intensity. However, despite the behavior observed in gas exchanges and reduction in the fluorescence levels of plants in the soil treated with sulfur and gypsum, due to the salinity of the soils after the treatment, there was no significant fit for the quantum efficiency of PSII, but the Fv/Fm levels were below 0.75 (Fig 2 D), which denotes damages in the photosynthetic apparatus of the sorghum plants (Baker and Rosenqvst, 2004;Lucena et al, 2012;Santos et al, 2014;Silva et al, 2014).…”
Section: Resultsmentioning
confidence: 89%